Menentukan Biaya Dan Waktu Pelaksanaan Erection Konstruksi Baja Mill Building Pabrik Kelapa Sawit - Silitonga, Desmon; Mardiaman, Mardiaman (Syntax Literate, 2025)
This research aims to assess the costs and duration associated with the erection of steel structures in the Mill Building of PT. Tunggal Yunus Estate Palm Oil Mill, located in Kampar, Riau. The palm oil sector plays a significant role in Indonesia's economy, making the presence of Palm Oil Mills (PKS) essential for palm oil production. Utilizing a quantitative methodology with a case study approach, the study analyzes work volume, equipment and labor productivity, as well as cost and time estimations. Results reveal that the erection period for the steel structure is 40 calendar days, which corresponds with the actual time recorded on-site. The overall cost of erection is IDR 276,075,000.00, resulting in a unit cost of IDR 1,854/kg. Various factors affecting costs and duration include weather conditions, the challenging muddy terrain of the project site, and the coordination among work teams. This study offers valuable insights for the planning and budgeting of future steel construction projects within the palm oil industry.